Current issues and corresponding optimizing strategies of layered oxide cathodes for sodium‐ion batteries - Xiang Tan; Jun Zeng; Luyi Sun; Chenxi Peng; Zheng Li; Shuhao Zou; Qian Shi; Hui Wang; Jun Liu (InfoMat)
Abstract Lithium‐ion batteries (LIBs) have dominated the market for a long time. However, the scarcity of lithium resources has sparked concerns about future energy storage devices, leading many researchers to turn their attention to other energy storage devices, such as sodium‐ion batteries (SIBs), potassium‐ion batteries (KIBs), zinc‐ion batteries (ZIBs), and so on. Among them, SIBs have attracted widespread attention from researchers due to their abundant sodium resources, high safety, and excellent low‐temperature performance. Because the cathode of the battery determines the energy density, cycle life, charge/discharge rate, and cost, the research on the cathodes for SIBs is particularly important. Layered oxide cathodes, with their periodic layered structure, good electrical conductivity, and two‐dimensional ion transport channels, are regarded as the most promising cathode materials for SIBs. Currently, the main issues facing layered oxide cathodes include irreversible phase transitions, high air sensitivity, insufficient energy density, surface residual alkali, and the migration and dissolution of transition metals. The key to solving these problems lies in the development of a new generation of high‐performance layered oxide cathodes. Hence, we review the current research progress of layered oxide cathode materials for SIBs and various optimizing strategies, and finally summarize and provide an outlook on the future development trends of SIBs.